Semantico-Functional Features of Expressive Derivatives in the Artistic Discourse of V. Makanin - S.Volskaya, Anastasia; A. Chupryakova, Olga; S. Safonova, Svetlana; T. Karipzhanova, Gulnaz (International Journal of Engineering and Technology, 2018)
The paper is devoted to the study of semantic and functional features of expressive derivatives, both usual and occasional, in the artistic gist of the novel â€œAsanâ€ by V. Makanin, as well as their role in structuring the individual-authorâ€™s linguistic picture of the world. It has been proven that the derivation of expressive lexemes is the result of improvisation according to established patterns, and that the formation of occasional substantives, adjectives and verbs involved the main methods of the Russian word derivation. It is noted that in the artistic discourse of V. Makanin, in the substantive word-formation, suffixation plays a leading role, which takes place in the sphere of abstractness and includes such lexical-semantic groups as expressive substantives with the meaning of a person, expressive substantives with the meaning of abstracted action or an abstract feature with connotation, as a rule, negative and/or reduced colloquial connotation. While in the sphere of adjectival and verbal word formation, confixation and prefixation, as the formation of expressiveness, is most productive. The paper considers the phenomenon of semantic word formation, describes the formation of semantic derivatives, including in the field of occasional vocabulary. Expressive derivatives in the artistic discourse of V. Makanin are a bright sign of his individual style, an important means of expressing the world view and outlook of the writer.Â Â